2017
DOI: 10.1128/iai.00239-17
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Nucleotidyl Cyclase Inhibits the Host Innate Immune Response by Suppressing TAK1 Activation

Abstract: Exoenzyme Y (ExoY) is a type III secretion system effector found in 90% of the isolates. Although it is known that ExoY is a soluble nucleotidyl cyclase that increases the cytoplasmic levels of nucleoside 3',5'-cyclic monophosphates (cNMPs) to mediate endothelial Tau phosphorylation and permeability, its functional role in the innate immune response is still poorly understood. Transforming growth factor β-activated kinase 1 (TAK1) is critical for mediating Toll-like receptor (TLR) signaling and subsequent acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 67 publications
(80 reference statements)
0
27
1
Order By: Relevance
“…The precise role of ExoY in P. aeruginosa infection still remains largely unclear. ExoY has been proposed to alter cell integrity leading to loss of endothelial cell barrier integrity (11,17), although more recent results suggest that it may also contribute to dampen the host innate immune responses (15,16). Inactivation of these ExoY functions may be beneficial at certain stages or forms of the bacterial infection.…”
Section: Terminus Of P Aeruginosa Exoymentioning
confidence: 99%
See 1 more Smart Citation
“…The precise role of ExoY in P. aeruginosa infection still remains largely unclear. ExoY has been proposed to alter cell integrity leading to loss of endothelial cell barrier integrity (11,17), although more recent results suggest that it may also contribute to dampen the host innate immune responses (15,16). Inactivation of these ExoY functions may be beneficial at certain stages or forms of the bacterial infection.…”
Section: Terminus Of P Aeruginosa Exoymentioning
confidence: 99%
“…In cell culture experiments, ExoY causes the formation of gaps between endothelial cells, thus increasing permeability of the endothelial monolayer in lungs (11,12) (yet these effects were not observed by other groups (13,14)). Very recently, two groups independently demonstrated that ExoY activity also leads to the inhibition of the host immune responses by suppressing the activation of TAK1 and decreasing the production of IL-1␤ (15,16). In vivo in animal models, ExoY was shown to cause severe lung damage in rats (17) and mice (18).…”
mentioning
confidence: 99%
“…During this early innate immune response, the stage is set for an effective mount of a host immune response against P. aeruginosa [ 24 , 25 ]. It has been documented that ExoY lowers concentrations of TNF and IL-1β after infection of rat lungs or epithelial cells, respectively [ 26 , 27 ]. Again, our data indicate that this dampening of the proinflammatory immune response within the infected organ already starts at 2-4 h after infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Exo Y impairs recovery of the endothelial cell barrier, decreasing migration, proliferation, and lung repair [151]. Exo Y, somewhat paradoxically, inhibits rather than induces pro-inflammatory cytokine and chemokine production in macrophages, as such decreasing secretion of IL-1β, IL-6, TNF, and of the chemokine IL-8/CXCL8 [154,155].…”
Section: Exotoxin Y (Exo Y)mentioning
confidence: 99%